On the origin of a remarkable increase in the strength and stability of an Al rich Al-Ni eutectic alloy by Zr addition. (15th May 2019) - Pandey, Prafull; Makineni, Surendra Kumar; Gault, Baptiste; Chattopadhyay, Kamanio
Abstract: The effect of Zr addition to Al rich binary α-Al - Al3 Ni eutectic cast alloy (Al-3.1 at.% Ni) in enhancing the microstructural stability and strength at high temperature is demonstrated. On subsequent heat treatment after casting, nanometric coherent L12 ordered Al3 Zr precipitates form inside the α-Al that strengthen the alloy. Additionally, remarkable stability of eutectic microstructure was observed even after 100 h of annealing at 400 °C. The synergetic effect of the strengthening of the α-Al matrix by coherent Al3 Zr precipitates and the low coarsening rate of the Al3 Ni rods results in a significant increase in high temperature hardness and yield strength of the alloy. The tensile yield strength of the annealed Al-3.1Ni-0.15Zr alloy (400 °C, 10 h) tested at 250 °C is found to be 185 ± 10 MPa, which is 1.5 times higher than the corresponding binary Al-3.1Ni alloy. The experimentally determined average rod size (radius) during annealing at 400 °C follows the classical matrix diffusion controlled LSW-based coarsening model for both binary Al-3.1Ni and ternary Al-3.1Ni-0.15Zr alloys. The calculated coarsening rate constant values based on modified LSW coarsening model are 10.3 and 4.1 nm 3 /s for Al-3.1Ni and Al-3.1Ni-0.15Zr alloys, respectively. Atom probe tomographic (APT) investigations of the heat-treated ternary alloy unambiguously reveal segregation of Zr solute at the αAl/Al3 Ni interface in addition to the presence of the strengthening Al3 Zr ordered precipitates in the α-Al matrix. The segregation hinders the interdiffusion of Al and Ni in the eutectic and, thereby, increasing the stability of the eutectic phase at high temperature. Graphical abstract: Image 1